Metabolism of 8-aminoquinoline antimalarial agents - Strother, A. (1981)
Some of the most effective antimalarial agents are derivatives of 8-aminoquinoline. The metabolic products of many of these compounds appear to be toxic to the erythrocytes of certain human subjects, especially those deficient in glucose-6-phosphate dehydrogenase. Although a number of studies have been conducted over many years, the metabolism of most of these compounds has not been determined. These studies are reviewed. Adult dogs dosed with tritium-labelled primaquine were observed to excrete approximately 16% of the injected radioactivity in the urine within 8 hours. Organic extracts of the urine were fractionated by thin-layer chromatography and the metabolic pattern obtained. Some primaquine was excreted along with at least five metabolites including 5-hydroxy-6-methoxy-8-(4-amino-1-methylbutylamino)quinoline (5HPQ) and a small amount of 6-hydroxy-8-(4-amino-1-methylbutylamino)quinoline (6HPQ). The 5HPQ could form a quinoneimine-type compound which may be a methaemoglobin-forming compound. This and other metabolites isolated from urine were found to be active methaemoglobin formers in in vitro studies. In vitro metabolism of primaquine by mouse liver enzymes also produced compounds capable of methaemoglobin formation. One of these had a blue colour when exposed to alkaline conditions, air, and light, and mass spectral data and nuclear magnetic resonance analysis indicated a structure similar to a 5,6-dihydroxy derivative of primaquine. However, the chemical structure of the metabolite was not identified in these studies.